(untitled) (NAU Journal of Technology and Vocational Education, 2026)
This study identified Entrepreneurship building needs of youths in greening TVET for workforce entry and environmental security in Benue State. Three research questions were raised and three hypotheses were formulated and tested at 0.05 alpha level. The study made use of survey research design and was carried out in Benue State. The instrument for data collection was a structured questionnaire made up of a 21-item titled “Entrepreneurship building needs of youths in greening TVET (EBNYG TVET)” and was administered on a112 respondents made up of 47 extension workers and 65 youths randomly selected from the entrepreneurship training Centres in the State. The data collected were analyzed using weighted mean, standard deviation and t-test statistics. From the analysis, it was revealed that youths: needed 5 skills in greening TVET, 4 entrepreneurship skills for workforce entry and 12 skills in environmental security. Testing of hypotheses revealed that there was generally no significant difference in the responses of youths and extension workers in Benue State. It was therefore, recommended among others, that the identified skills be packaged into workshop materials and bulletins for youths. The extension workers should use the materials for training and retraining youths in the registered centers.